On the Spatial Semantics of the Russian Verb Prefix pod-: A CrosslinguisticAnalysis Based on Data from the Russian-Italian Parallel Corpus of the RNC - Zangoli, Giulia (Slavistica Vilnensis, 2025)
In our study, we have investigated the semantic contribution of the Russian verb prefix pod- in encoding the approach to the goal of motion in a crosslinguistic perspective. We have focused on the semantic components of Path encoded by the prefix pod- and on their corresponding elements in Italian translation. Specifically, we have examined the role of pod- when combined with Russian verbs that express definite motion. By using the Russian-Italian parallel corpus from the Russian National Corpus, we have analysed the contexts in which the prefix pod- is used, as well as the locative arguments it combines with to encode the goal of motion, and how its semantic contribution can be expressed in Italian. Our study represents a preliminary exploration of the semantic contribution of the prefix pod- in a crosslinguistic perspective, and it does not aim to provide an exhaustive account of the subject. Our aim is to determine which Path components encoded by the prefix pod- can be translated into Italian. Preliminary data analysis suggests that the focus in Italian texts may vary depending on the context and on the landmarks’ characteristics: either emphasizing the spatial contribution of pod- as a whole or highlighting one of its specific semantic components. In other words, the semantic complexity of pod- may be only partially encoded in Italian translation.
Keywords: verbal semantics; lexicalization of approximation; final point; Russian language; Italian language; prefixes